2021
DOI: 10.1007/s00401-021-02327-x
|View full text |Cite
|
Sign up to set email alerts
|

Targeting fibroblast growth factor receptors to combat aggressive ependymoma

Abstract: Ependymomas (EPN) are central nervous system tumors comprising both aggressive and more benign molecular subtypes. However, therapy of the high-risk subtypes posterior fossa group A (PF-A) and supratentorial RELA-fusion positive (ST-RELA) is limited to gross total resection and radiotherapy, as effective systemic treatment concepts are still lacking. We have recently described fibroblast growth factor receptors 1 and 3 (FGFR1/FGFR3) as oncogenic drivers of EPN. However, the underlying molecular mechanisms and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 74 publications
1
17
0
Order By: Relevance
“…FGFR3 , a gene located on chromosome 4 and responsible for bone development, has been shown to be overexpressed in an in-vitro model of ST-ZFTA. This study also demonstrated the efficacy of a broad range of FGFR inhibitors in inducing maturation in their invitro model, a therapeutic concept currently considered of high potential in pediatric cancers [ 192 ]. Lastly, immune checkpoint molecules are another possible target currently being investigated.…”
Section: Supratentorial Ependymoma With Zfta-fusion (St-zfta)mentioning
confidence: 91%
“…FGFR3 , a gene located on chromosome 4 and responsible for bone development, has been shown to be overexpressed in an in-vitro model of ST-ZFTA. This study also demonstrated the efficacy of a broad range of FGFR inhibitors in inducing maturation in their invitro model, a therapeutic concept currently considered of high potential in pediatric cancers [ 192 ]. Lastly, immune checkpoint molecules are another possible target currently being investigated.…”
Section: Supratentorial Ependymoma With Zfta-fusion (St-zfta)mentioning
confidence: 91%
“…Thus far, no targeted therapies are available in ependymomas. A recent preclinical study has suggested FGFR inhibition as a novel approach to target aggressive ependymomas [ 46 ].…”
Section: Management Of Newly Diagnosed Intracranial Ependymomas In Ch...mentioning
confidence: 99%
“…High throughput drug screening in murine models of ZFTA fusion-negative supratentorial ependymoma, characterized by the Ephb2 oncogene identified 5-fluoracil (5-FU) as a potential active drug against this subtype [ 174 , 175 ]. Fibroblast growth factor receptor inhibitors have also been shown to have activity against patient derived ependymoma cell models and demonstrate efficacy in the clinic [ 176 ]. As detailed above, the use of histone deacetylase inhibitors as differentiation therapy is currently under evaluation in the current SIOP-Europe trial, following in vitro analyses [ 177 , 178 ].…”
Section: Ependymomamentioning
confidence: 99%